El doble personaje del planeta Venus en las religiones indígenas del Gran Nayar: mitología, ritual agrícola y sacrificio - Johannes Neurath (Journal de la Société des Américanistes)
The double personality of planet Venus in indigenous religions of the Gran Nayar: mythology, agricultural rites, and sacrifice. Indigenous religion of West Mexico’s Gran Nayar region offers important clues for understanding Ancient Mesoamerica’s cults of planet Venus. The fact that among Cora-Indians, and, to a lesser extent, among Huichols and local Nahuas, Venus-related mythology has been maintained should not be taken as something circumstantial. Rather, the periodic transformations of Morning and Evening Star corroborate a main cultural paradigm. The very particular way the antagonism between the two aspects of one astral deity is understood can be taken as a conceptual model explaining a whole range of religious practices and believes, from agricultural and rain-related ceremonies to ritual deer-hunt and sacrifice.